Fabricated of bimetallic Pd/Pt nanostructure deposited on copper nanofoam substrate by galvanic replacement as an effective electrocatalyst for hydrogen evolution reaction. (8th June 2015) - Rezaei, Behzad; Mokhtarianpour, Maryam; Ensafi, Ali Asghar
Abstract The effective Pd/Pt bimetallic nanofoam catalyst (Pd/Pt NFC) was fabricated on Cu nanofoam substrate. The substrate was electrochemically prepared by copper reduction and covered with Pd/Pt NFC by galvanic replacement reaction in aqueous solutions of Pd (II) and Pt (IV). The catalyst was characterized by SEM, EDX, ICP-OES and EIS techniques. It was tested for the hydrogen evolution reaction (HER) in the acidic media by linear sweep voltammetry (LSV). Among of various compositions, Pd65Pt35 catalyst showed better performance in comparison with pure Pt NFC for HER. The mass activity of noble metals on the Pt NFC and Pd65Pt35 NFC, at the same potential of −300 mV vs. NHE, were about 3.21 mA μg−1Pt and 4.98 mA μg−1Pt+Pd, respectively. Consequently, proposed catalyst increased HER activity about 1.5 times and decreases Pt loading on the surface and cost of catalyst. The obtained results show that the Volmer-Heyrovsky mechanism controls the HER. The fabricated catalyst showed a good stability for HER by chronoamperometric method.